THE CAREGIVING EXPERIENCES OF OLDER ADULTS IN LIVING-APART-TOGETHER RELATIONSHIPS - Benson, J J (Innov Aging, 2018)
Adults looking for new romantic partnerships in later life often prefer the flexible arrangement of living-apart-together (LAT) to traditional marriage or cohabitation. Most of our empirical understanding of these relationships is limited to descriptive accounts of participants’ reasons for choosing to LAT. This study explores the caregiving roles of LAT couples in later life. Fifteen men and women aged 64 to 92 completed semi-structured interviews about their LAT partner caregiving experiences. Nine caregivers reported episodic caregiving experiences, whereas six described caregiving at end-of-life or in the context of a life-limiting illness. Most caregivers reported making adjustments to their living arrangements or extending visitation to better facilitate care delivery. A common theme within the caregiver narratives was the concept of gatekeeping and the privilege associated with being a biological/legal family member—family members appeared to dictate the degree of LAT caregiver involvement, especially as caregiving needs of the infirm partner intensified.